Update of Genetic and Molecular Causes of Adrenocortical Hyperplasias Causing Cushing Syndrome - Berthon, Annabel; Bertherat, Jérôme (Hormone and Metabolic Research, 2020)
Bilateral hyperplasias of the adrenal cortex are rare causes of chronic endogenous hypercortisolemia also called Cushing syndrome. These hyperplasias have been classified in two categories based on the adrenal nodule size: the micronodular types include Primary Pigmented Nodular Adrenocortical Disease (PPNAD) and isolated Micronodular Adrenal Disease (iMAD) and the macronodular also named Primary Bilateral Macronodular Adrenal Hyperplasia (PBMAH). This review discusses the genetic and molecular causes of these different forms of hyperplasia that involve mutations and dysregulation of various regulators of the cAMP/protein kinase A (PKA) pathway. PKA signaling is the main pathway controlling cortisol secretion in adrenocortical cells under ACTH stimulation. Although mutations of the regulatory subunit R1α of PKA (PRKAR1A) is the main cause of familial and sporadic PPNAD, inactivation of two cAMP-binding phosphodiesterases (PDE11A and PDE8B) are associated with iMAD even if they are also found in PPNAD and PBMAH cases. Interestingly, PBMAH that is observed in multiple familial syndrome such as APC, menin, fumarate hydratase genes, has initially been associated with the aberrant expression of G-protein coupled receptors (GPCR) leading to an activation of cAMP/PKA pathway. However, more recently, the discovery of germline mutations in Armadillo repeat containing protein 5 (ARMC5) gene in 25–50% of PBMAH patients highlights its importance in the development of PBMAH. The potential relationship between ARMC5 mutations and aberrant GPCR expression is discussed as well as the potential other causes of PBMAH.
Keywords: Cushing syndrome; PPNAD; PBMAH; iMAD; PRKAR1A; ARMC5